The Theory of Phonologically Relevant Features and the “Phonetic Metonymy” - Раевский, М. В. (Kalbotyra, 1987)
In current theories of DFs a chiefly articulatory phonetic terminology is made use of. This leads inevitably to the substitution of the description of the elementary movements of the organs of speech for the real object of investigation, the DFs of phonemes. The inventory of the functionally relevant sound features may be established only on the basis of a detailed investigation of the processes of speech perception.